PELAKSANAAN LITERASI SEKOLAH PADA MATA PELAJARAN EKONOMI KELAS X MA KHULAFAUR RASYIDIN KUBU RAYA - Yana, Syarifah Rema; Khosmas, F. Y; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is entitled "implementation School Literacy on economic subjects in Class X Madrasah Aliyah Khulafaur Rasyidin Kubu Raya". This research aims to study How School Literacy in Class X Madrasah Aliyah Khulafaur Rasyidin Kubu Raya. The research method used in this study is a qualitative description. Data collection tools use observation, interview guides, and documentation. The results of this study indicate: The program of implementing school literacy in Madrasah Aliyah Khulafaur Rasyidin Kubu Raya up to three people, namely: 1) The habituation stage which is to foster interest in reading 15 minutes of reading non-lesson books; 2) The development stage is students who analyze or re-discuss the books they have read; 3) The learning phase is a general knowledge textbook of enrichment reading books and textbooks such as Indonesian, mathematics, religion etc.Â Keywords: Implementation, School Literacy, Economic